Study on the Performance of Signaled Intersections in the City of Bandar Lampung (Case Study of JL. Sultan Agung - Kimaja Intersection durig Covid-19 - Pramita, Galuh; Lestari, Fera; Bertarina, Bertarina (Jurnal Teknik Sipil, 2020)
Transportation has a part important in supporting community activities in a country. The transportation problem in Indonesia is one that is difficult to handle. The city of Bandar Lampung has a congestion problem that occurs at signaled intersections. One of the Traffic congestion  occurred at the   Sultan Agung "“ Kimaja Intersection.  Now, Indonesia be stricken by Covid-19 pandemic. During the pandemic, the community mus be carried out physical distancing. The aim of this research  to find out the performance and evaluate the congestion at intersection signalized during the covid-19 pandemic. The data used is volume of traffic during peak hours. The calculation of the performance of the intersection of Sultan Agung - Kimaja, it can be seen that the maximum traffic flow is 779 pcu / greater than the capacity that can be accommodated, which is 376 pcu / hour. The degree of saturation at each intersection approach is the north approach 0.97 and the south approach 0.85 with service level E. For the western approach is 1.67 and the eastern approach is 1.06 with the level of service on the approach is category F.